2020
DOI: 10.1055/s-0040-1709477
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction Using Free Flaps for Diabetic Heel Defects: Outcomes and Risk Factor Analysis

Abstract: Background Overall success rate after diabetic foot reconstruction using free flap has been acceptable, but certain parts of the foot like the heel remains more challenging. Patients and Methods This retrospective study reviewed 37 patients reconstructed with free flaps for diabetic foot ulcer on the heel region from 2008 to 2017. Flap outcome in addition to various risk factors were analyzed; arterial status on heel, the American Society of Anesthesiologists (ASA) physical status, smoking, hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…There is still lacking evidence on independent factors influencing the outcome in free flap transfer to the forefoot. Only three studies limited to diabetic foot defects investigated possible risk factors for postoperative complications [21][22][23] . Oh et al 21 investigated 121 cases of microsurgical diabetic foot reconstruction and identified peripheral arterial disease, a history…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still lacking evidence on independent factors influencing the outcome in free flap transfer to the forefoot. Only three studies limited to diabetic foot defects investigated possible risk factors for postoperative complications [21][22][23] . Oh et al 21 investigated 121 cases of microsurgical diabetic foot reconstruction and identified peripheral arterial disease, a history…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Las et al 25 reviewing possible risk factors in 330 microsurgical lower extremity reconstructions arterial hypertension trended towards significancy in univariate analysis while no significance was shown in multivariate analysis. Other previous studies focusing on microsurgical extremity reconstruction could not find an association of hypertension with flap failure 22,26,31 or did not include arterial hypertension in their risk factor analysis 23,32,33 .…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The subsequent cycle of progressive infection and deformity eventually result in crippling LE morbidity in these patients (Kadam & Microsurg, 2016;Kallio et al, 2015). Delayed healing may lead to higher amputation rates, with diabetic patients accounting for 40%-70% of all lower limb amputations (Eskelinen et al, 2015;Kim et al, 2020). Goals of surgical management of heel ulcers should include early intervention to (1) control infection, (2) promote ulcer healing, and (3) prevent future recurrences (Younes et al, 2004); we highlight the role of reconstruction during early intervention to prevent morbidity such as amputation.…”
Section: Introductionmentioning
confidence: 99%
“…The heel serves a vital purpose in functionality as the most important weight-bearing region of the foot and the key point for ambulation (Kim et al, 2020). Therefore, salvage of the heel is critical in preservation of gait and ambulation.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a common, chronic, neurovascular disease that is challenging to treat because patients can have many serious complications, including diabetic foot ulcers (DFU) (1,2). site of DFU which are characterized by wounds that reach the deep anatomical layers, a long disease course, and repair difficulties (4). Advancements in microscopic techniques have promoted the widespread clinical application of different perforator flaps for the treatment of DFU.…”
Section: Introductionmentioning
confidence: 99%